2007
DOI: 10.1128/cvi.00311-06
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Spiramycin Treatment and Gestational Age on Maturation ofToxoplasma gondiiImmunoglobulin G Avidity in Pregnant Women

Abstract: The objective of the present study was to investigate the maturation of immunoglobulin G (IgG) avidity after Toxoplasma gondii seroconversion during pregnancy and the factors that affect IgG avidity over time. The study used 309 serum samples from 117 women and a multiple linear mixed regression analysis to show the patterns of variation of IgG avidity throughout gestation. The IgG avidity ratios and the patterns of their evolution with time were quite diverse among the women and were statistically heterogeneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
0
23
0
2
Order By: Relevance
“…15,16 Many factors have been found to influence the progression from low to high avidity. [23][24][25][26] A low avidity result with the assay described in this paper suggested that a recent HCV infection has occurred within ∼4-5 months. In this study, group 1 (acute patients) were defined as becoming anti-HCV positive after a previous negative result taken 4-6 months ago.…”
Section: Discussionmentioning
confidence: 75%
“…15,16 Many factors have been found to influence the progression from low to high avidity. [23][24][25][26] A low avidity result with the assay described in this paper suggested that a recent HCV infection has occurred within ∼4-5 months. In this study, group 1 (acute patients) were defined as becoming anti-HCV positive after a previous negative result taken 4-6 months ago.…”
Section: Discussionmentioning
confidence: 75%
“…However, when the avidity index is low or intermediate, the interpretation is ambivalent, since it cannot exclude an infection acquired in the preceding 4 months but also cannot prove that it is recent, unless the index is extremely low. From this standpoint, it should be kept in mind that treatment delays IgG avidity maturation (202). In a study by Petersen et al (253), the mean IgG avidity index determined during the 16 weeks following infection was lower in treated pregnant women than in untreated nonpregnant patients (0.092 versus 0.149; P Ͻ 0.01).…”
Section: Serologic Techniques and Interpretation (I) A Wide Range Ofmentioning
confidence: 97%
“…Another way to appreciate the age of infection resides in the kinetics of IgG titers analyzed in two serum samples obtained at 3-week intervals in the absence of any specific therapy. Rising IgG titers are suggestive of an infection acquired less than 2 months before the earlier sample, but one must be aware that treatment may also reduce or abolish the increase of IgG titers (202). Combinations of different diagnostic tools and clear-cut interpretations are necessary to achieve an accurate dating of infection and safe counseling for pregnancy management (Fig.…”
Section: Serologic Techniques and Interpretation (I) A Wide Range Ofmentioning
confidence: 99%
“…When such a scenario is observed in pregnant women, this leads us to consider the possibility of a recent infection, rendering it essential to confirm this infection before implementing a treatment designed to decrease fetal transmission and involvement (51,52). The AxSYM and Elecsys IgG assays were found to be the most efficient methods in the patients in whom a seroconversion was assessed (Tables 5 and 6).…”
Section: Discussionmentioning
confidence: 99%